Project management for small projects, second edition - Rowe, Sandra F. 1961- (Management Concepts Press, 2015)
This new edition is updated throughout to reflect the PMBOK Guide, fifth edition, balancing the particular needs of small projects with the project management methodology. Project managers who are proficient at managing and leading their own projects are increasingly being called upon to work collaboratively with other project managers to lead components of a program. In addition to knowing how to manage processes and how to lead the team, project managers must now also know how to collaborate and share knowledge with other project managers. A new chapter on program management offers important insights and guidance for managing a group of related small projects in a coordinated way to obtain benefits and control not available from managing them individually. --